Clinical Study on strangles in Iraqi horses - A., Jawad, N.M. (The Iraqi Journal of Veterinary Medicine, 2000)
Ten young horses (6 males , 4 females ), 2-2.5 years old infected with stangles were used in this study . The clinical signs were obvious . Strp vacc-5 vaccine was used intramuscularty and the animals were kept under clinical observation for two weeks. The clinical signs disappeared from all vaccinated animals within 8 days, and the vaccine gave good positive results. It was recommended to use it for treatment and vaccination at the same time .